Migration Results to a Private Cloud by using the M2CCF - Cardoso, Abílio (2017)
The cloud computing paradigm is transforming the way IT services are provided and consumed by changing IT products to services. The migration of in-house IT services to cloud computing must be performed carefully so as not to cause high losses in the institution. In this paper, we present the use of the framework developed by the same authors, to the migration of services, applications, data and infrastructures to cloud computing, M2CCF, compatible with Information Technology Infrastructure Library (ITIL). The work also discusses the results gathered from the real implementation of the framework in the migration of IT services to a private cloud.